The utilization of aloe vera (aloe barbandensis miller) influencing itch reducton in pregnant woman) - Herawati, Yanti; Kartika, Ira; Ratminah, Mien; Herlina, Lina (MEDIA ILMU KESEHATAN, 2024)
Background: Striae gravidarum happens during the 18th week to the 32nd week in pregnant women, this is as a result of over distance of abdominal wall. Striae Gravidarum inextricably linked with relaxin hormone. Human chorionic gonadotropin will increase the secretion of relaxin. Secretion of this hormone will decrease following the 24th week, consequently the risk of developing Striae gravidarum becomes higher. It may result in itch, in the worst case of Striae gravidarum itching.Objective: To determine the influence of Aloe Vera (Aloe Barbadensis Miller) usage on itch reduction in pregnant women with striae gravidarum.Methods: Using a one-group pretest-posttest design methodology, this study employed a quasi-experiment design. Thirty responders were among the samples. This study took place in May 2023. Itching score was measured using VAS. Paired T-test was used for data analysis.Results: Average of itching frequency prior to the use of aloe vera was 8.27, upon the use of aloe vera its average was 2.97cc. The mean of measurement difference before and after was 5.3.Conclusion: The application of aloe vera demonstrates efficacy in alleviating itching in expectant mothers experiencing striae gravidarum